A Commentary on Kant’s Introduction of the Concept of Transcendental Deduction - Woleński, Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The aim of this paper is to show the place of legal analogy in Kant’s introduction of the concept of transcendental deduction. After remarks on Kant’s use of the term “deduction,” transcendental deduction is characterised as the method justifying necessary statements about objects. It is argued that this method has normative elements. This leads to asserting similarities between epistemic obligation and legal obligation in the framework of transcendental philosophy.